Mesoporous carbon carrier for fuel cell, preparation method and catalyst based on carrier
Through the process of first calcining, then acidizing pore expansion and single impregnation carbonization method, the batch difference and stability problems in the preparation of mesoporous carbon support are solved, and the performance uniformity and production efficiency of the catalyst are improved.
Patent Information
- Application Number
- CN202411351622.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-10
AI Technical Summary
There are batch differences and uncertainty in the preparation methods of existing mesoporous carbon, resulting in uneven catalyst performance, and complicated steps for multiple impregnation and replication, and low efficiency.
The chain-shaped mesoporous silica template was prepared by a process of empty calcining and then acidizing and reaming. The hydroxyl low-boiling point solvent and initiator were combined for single impregnation and carbonization. After removing the template, the mesoporous carbon support was prepared to improve batch stability. and productivity.
The batch stability and production efficiency of mesoporous carbon support are improved, experimental steps are reduced, and the performance uniformity and stability of the catalyst are improved.
Smart Images

Figure CN119297310A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of fuel cell catalysts, and in particular relates to a mesoporous carbon carrier for fuel cells, a preparation method and a catalyst based on the carrier. Background Art
[0002] The key technical membrane electrode materials in hydrogen fuel cells include gas diffusion layers, catalysts, polymer ionomer membranes, etc. The catalyst in the membrane electrode of hydrogen fuel cells is usually composed of platinum that catalyzes hydrogen reactions loaded on conductive carbon materials. Currently, the commonly used conductive carbon materials as catalyst carriers for hydrogen fuel cells include solid carbon, mesoporous carbon, and porous carbon.
[0003] Among them, the existing mesoporous carbon preparation process can produce mesoporous carbon with a connection structure and optimized pore size, pore capacity and linearity as a catalyst carrier, and can obtain an air electrode catalyst layer with a moderate thickness and an appropriate amount of voids, thereby suppressing overflow. However, the existing preparation method does not adequately treat the post-treatment of mesoporous silica, which will lead to batch differences in subsequent pore expansion, and thus lead to batch differences in the prepared mesoporous carbon. Each batch needs to adjust the process according to actual experience, and there is uncertainty in the batch and stability of the prepared mesoporous carbon carrier; at the same time, the method of impregnation with only sugar alcohol in the carbon source impregnation synthesis will also lead to performance differences in large electric density between batches of carbon black.
[0004] Based on this, a new preparation process of mesoporous carbon carrier is studied to achieve the stability of mesoporous carbon quality between batches and between different groups in batches, and to improve the stability and uniformity of catalyst performance. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a new type of mesoporous carbon carrier, which can not only achieve the stability of mesoporous carbon between batches and between different groups in batches through process improvement, but also can obtain a sufficient amount of mesoporous carbon by a single impregnation carbonization, thereby improving the production efficiency and stability during production.
[0006] Technical solution: The mesoporous carbon carrier for fuel cells of the present invention has a total specific surface area of 1400-2000m 2 / g, the average pore size is 4-7nm, and the average particle size is 100-300nm.
[0007] The method for preparing the mesoporous carbon support for fuel cells according to claim 1 of the present invention is characterized by comprising the following steps:
[0008] (1) Preparation of chain-shaped mesoporous silica;
[0009] (2) heat treating the chain-shaped mesoporous silica in an air atmosphere at 500-600° C. for 3-8 hours, and then acidifying and expanding the pores with sulfuric acid to obtain a mesoporous silica template;
[0010] (3) The mesoporous silica template is mixed with a carbon source, a low-boiling point solvent having a hydroxyl group and an initiator, and is first stirred and heated at 30-50° C. for 2-3 hours, and then heated and polymerized at 80-100° C. for 8-15 hours. After carbonization, the mesoporous silica template is removed, and heat treatment is performed to obtain a mesoporous carbon carrier.
[0011] The present invention first uses a large amount of surfactants to prepare chain-shaped mesoporous silica, based on which, the surfactants are completely removed by first air burning and then acid washing and pore expansion, and sulfuric acid is used to perform pore expansion treatment to further adjust the pore structure of silica to the desired appropriate range; that is, by first air burning, the organic matter and oxygen-containing functional groups remaining on the surface of silica are oxidized and calcined to be completely removed, and then acid washing and pore expansion are performed, which reduces the heterogeneity of the organic matter and oxygen-containing functional groups remaining on the surface of silica on the pore expansion, and avoids the inability to form the same structure. Mesoporous carbon causes structural heterogeneity and quality instability of mesoporous carbon between different batches and between different groups in a batch; on the other hand, by first burning in air and then expanding the pores with acid, the silica is subjected to a certain oxidation treatment on the basis of further expanding the pores of the silica with sulfuric acid, so that a certain amount of oxygen-containing functional groups exist on the surface of the silica, which combine with the low-boiling point solvent with hydroxyl groups used in the subsequent carbon source impregnation, providing a better wetting effect, and being able to obtain a sufficient amount of mesoporous carbon through a single impregnation carbonization, avoiding multiple impregnations to achieve full replication of the template, reducing the number of experimental steps, and improving efficiency.
[0012] Furthermore, the chain-shaped mesoporous silica of the present invention is prepared by the following steps:
[0013] ① Evenly mix deionized water, organic alcohol and surfactant to prepare mixed solution I; the mass ratio of deionized water to surfactant is (12-30):1;
[0014] ② Add the alkaline solution to the mixed solution I and stir for 0.5-1h to obtain the mixed solution II;
[0015] ③ After mixing the silicon source and the organic alcohol, a mixed solution III is prepared, and the mixed solution III is added to the mixed solution II, and the reaction is stirred at 40-80° C. for not less than 2 hours, and then filtered and dried to obtain chain-shaped mesoporous silica; the mass ratio of the silicon source to the organic alcohol is 1:(8-15);
[0016] In the steps ① to ③, the organic alcohol is methanol and ethylene glycol in a mass ratio of (1-4):1, and the mass ratio of the total amount of the organic alcohol to water in steps ① and ③ is 1:(1-2); the mass ratio of the alkaline solution, the surfactant and the silicon source is (0.46-0.7):(0.7-1):1.
[0017] Further, the surfactant of the present invention includes hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide or nonyltrimethylammonium halide; the alkali is sodium hydroxide, potassium hydroxide, ammonia water or triethylamine; the silicon source is tetraethyl orthosilicate, tetraethoxysilane, tetraisopropoxysilane or dimethoxydiethylsilane.
[0018] Furthermore, the present invention uses sulfuric acid for acidification and pore expansion, and the acid pickling treatment is carried out for 48-72 hours under the conditions of acid concentration of 1-3M and acid pickling solid content of 0.5-2%.
[0019] Furthermore, the mass ratio of the solvent to the mesoporous silica template of the present invention is (3-5):1, the mass ratio of the initiator to the carbon source is 1:(100-800), and the mass ratio of the mesoporous silica template to the carbon source is 1:(0.5-2).
[0020] Furthermore, the solvent of the present invention is water, ethanol, methanol or isopropanol; the carbon source is xylitol, maltitol, glucose or sucrose; and the initiator is acetic acid, oxalic acid, acetic acid, hydrochloric acid or sulfuric acid.
[0021] Furthermore, the carbonization of the present invention is carried out at 350-900° C. for 4-6 hours.
[0022] Furthermore, the heat treatment of the present invention is a heat treatment at 500-2300° C. for 1-3 hours.
[0023] The fuel cell catalyst of the present invention comprises the above-mentioned mesoporous carbon carrier and platinum loaded on the mesoporous carbon carrier, and the loading amount of platinum is 40-70%.
[0024] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the mesoporous carbon carrier can not only achieve the stability of mesoporous carbon between batches and between different groups in batches through process improvement, but also can obtain a sufficient amount of mesoporous carbon by a single impregnation carbonization, thereby improving the production efficiency and stability during production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the mesoporous silica prepared in Example 1 of the present invention;
[0026] Figure 2 This is a SEM image of the mesoporous carbon prepared in Example 1 of the present invention;
[0027] Figure 3 This is a BET data diagram of the mesoporous carbon prepared in Example 1 of the present invention;
[0028] Figure 4 Polarization curves of catalysts prepared using Example 1 and Comparative Examples 1-3 as carriers;
[0029] Figure 5 Polarization curves of the catalysts tested using Examples 1-4 of the present invention as carriers. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0031] It should be noted that the raw materials used in the present invention can all be purchased from commercial sources.
[0032] The mesoporous carbon carrier for fuel cells prepared by the present invention has a total specific surface area of 1400-2000m 2 / g, the average pore size is 4-7nm, and the average particle size is 100-300nm.
[0033] The carbon source used in the following embodiments of the present invention may be xylitol, maltitol, glucose or sucrose. The solvent may be water, ethanol, methanol or isopropanol. The initiator may be acetic acid, oxalic acid, acetic acid, hydrochloric acid or sulfuric acid. The surfactant may be hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide or nonyltrimethylammonium halide; the base may be sodium hydroxide, potassium hydroxide, ammonia or triethylamine; the silicon source may be tetraethyl orthosilicate, tetraethoxysilane, tetraisopropoxysilane or dimethoxydiethylsilane.
[0034] The chain-shaped mesoporous silica of the present invention is prepared by the following steps:
[0035] ① Evenly mix deionized water, an organic alcohol and a surfactant to prepare a mixed solution I; the mass ratio of the deionized water to the surfactant is (12-30):1, preferably (20-30):1;
[0036] ② Adding alkaline solution to mixed solution I and stirring for 0.5-1h, preferably 0.5h, to obtain mixed solution II;
[0037] ③ After mixing the silicon source and the organic alcohol, a mixed solution III is prepared, and the mixed solution III is added to the mixed solution II, and the reaction is stirred at 40-80° C. for not less than 2 hours, and then filtered and dried to obtain chain-shaped mesoporous silica; the mass ratio of the silicon source to the organic alcohol is 1:(8-15);
[0038] In the above steps ① to ③, the organic alcohol is methanol and ethylene glycol in a mass ratio of (1-4):1, preferably (2-4):1. The mass ratio of the total amount of organic alcohol to water in steps ① and ③ is 1:(1-2), preferably 1:(1-1.5); the mass ratio of the alkaline solution, the surfactant and the silicon source is (0.46-0.7):(0.7-1):1, preferably (0.5-0.64):(0.7-1):1.
[0039] The method for preparing a mesoporous carbon carrier for a fuel cell of the present invention comprises the following steps:
[0040] (1) Preparation of chain-shaped mesoporous silica;
[0041] (2) heat treating the chain-shaped mesoporous silica in an air atmosphere at 500-600° C. for 3-8 hours, and then acidifying and expanding the pores with sulfuric acid to obtain a mesoporous silica template;
[0042] (3) The mesoporous silica template is mixed with a carbon source, a low boiling point solvent having a hydroxyl group and an initiator, and is first stirred and heated for 2-3 hours at 30-50° C., and then heated and polymerized at 80-100° C. for 8-15 hours, preferably 8-12 hours, and then carbonized, the mesoporous silica template is removed, and heat treated to obtain a mesoporous carbon support. The mass ratio of the initiator to the carbon source is 1:(100-800), preferably 1:(200-400).
[0043] Example 1
[0044] The preparation method of the mesoporous carbon carrier of Example 1 comprises the following steps:
[0045] (1) Preparation of chain-like mesoporous silica:
[0046] ① Weigh 476g of deionized water, 142.7g of methanol and 71.3g of ethylene glycol, mix them evenly, add 22.355g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0047] ② Add 16.832 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, mix and stir for 0.5 h to obtain a mixed solution II;
[0048] ③ Add a solution uniformly mixed with 26.3 g of tetraethyl orthosilicate, 30 g of ethylene glycol and 60 g of methanol, react at 40° C. for 2 h, filter and dry to obtain chain-shaped mesoporous silica.
[0049] (2) Preparation of mesoporous silica template:
[0050] The chain-shaped mesoporous silica prepared in step (1) is placed in an atmosphere furnace for heat treatment, i.e., treated at 550°C for 3h in an air atmosphere; then a pore expansion treatment is performed, i.e., 350ml×1.5M sulfuric acid is added to a round-bottom flask, the solid content is 1%, and the acidification treatment is performed by oil bath heating at 100°C×72h; finally, the sample is washed and dried until the conductivity is less than 3us / cm, and the sample is dried at 60°C×18h to obtain a mesoporous silica template.
[0051] (3) Preparation of mesoporous carbon carrier:
[0052] Take 4g of the mesoporous silica template prepared in step (2), add 6g of sugar alcohol, 14g of water and 21mg of acetic acid, mix well, and stir in an oil bath at 40°C for 2h; then raise the temperature to 80°C and stir for polymerization for 8h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 900°C at 2°C / min, and keep warm for 4h. In 200ml, 1M sodium hydroxide solution, stir at 60°C in a water bath for 4h, remove the template, and then filter, wash, and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 900°C at 5°C / min, and keeping warm for 3h.
[0053] Example 2
[0054] The other steps and parameters are the same as those in Example 1, except that in step (1), the mass ratio of water to organic mixed alcohol is 1.6:1, wherein the mass ratio of methanol to ethylene glycol is 3:1.
[0055] Example 3
[0056] The other steps and parameters are the same as those in Example 1, except that in step (1), the mass ratio of the sodium hydroxide aqueous solution, the surfactant and tetraethyl orthosilicate is 0.5:0.85:1.
[0057] Example 4
[0058] The other steps and parameters are the same as those in Example 1, except that in step (3), the mass ratio of solvent water to mesoporous silica is 3:1.
[0059] Comparative Example 1 - Adjust the post-treatment process sequence, pickling first and then empty firing
[0060] The preparation method of the mesoporous carbon carrier of Comparative Example 1 comprises the following steps:
[0061] (1) Preparation of chain-like mesoporous silica:
[0062] ① Weigh 476g of deionized water, 142.7g of methanol, and 71.3g of ethylene glycol, mix well, add 22.355g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0063] ② Add 16.832 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, and mix and stir for 0.5 h to obtain a mixed solution II;
[0064] ③ Add a solution uniformly mixed with 26.3 g of tetraethyl orthosilicate, 30 g of ethylene glycol and 60 g of methanol, react at 40° C. for 2 h, filter and dry to obtain chain-shaped mesoporous silica.
[0065] (2) Preparation of mesoporous silica template:
[0066] The silica prepared in step (1) is subjected to an acidification treatment at 100°C for 72 h in 350 ml × 1.5 M sulfuric acid. After the treatment, the sample is washed until the conductivity is less than 3 us / cm, and the sample is dried at 60°C for 18 h. Finally, a heat treatment is performed in an atmosphere furnace at 550°C for 3 h in an air atmosphere to obtain a mesoporous silica template.
[0067] (3) Preparation of mesoporous carbon carrier:
[0068] Take 4g of the mesoporous silica template prepared in step (2), add 6g of sugar alcohol, 14g of water and 21mg of acetic acid, mix well, stir and mix at 40℃ in an oil bath for 2h; then raise the temperature to 80℃, stir and polymerize for 8h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 900℃ at 2℃ / min, and keep warm for 4h. Stir in a water bath at 60℃ for 4h in 200ml, 1M sodium hydroxide solution, remove the template, filter, wash and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 900℃ at 5℃ / min, and keeping warm for 3h.
[0069] Comparative Example 2 - Changing the acidification and pore expansion conditions in the post-treatment process and using hydrothermal pore expansion
[0070] The preparation method of the mesoporous carbon carrier of Comparative Example 2 comprises the following steps:
[0071] (1) Preparation of chain-like mesoporous silica:
[0072] ① Weigh 476g of deionized water, 142.7g of methanol and 71.3g of ethylene glycol, mix them evenly, add 22.355g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0073] ② Add 16.832 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, mix and stir for 0.5 h to obtain a mixed solution II;
[0074] ③ Add a solution uniformly mixed with 26.3 g of tetraethyl orthosilicate, 30 g of ethylene glycol and 60 g of methanol, react at 40° C. for 2 h, filter and dry to obtain chain-shaped mesoporous silica.
[0075] (2) Preparation of mesoporous silica template:
[0076] The mesoporous silica prepared in step (1) is heat-treated in an atmosphere furnace at 550°C for 3 hours under an air atmosphere; then a pore expansion treatment is performed by adding 350 ml×1.5 M sulfuric acid into a hydrothermal kettle, acid washing with a solid content of 1%, and acidification treatment at 100°C for 72 hours; finally, the sample is washed and dried until the conductivity is less than 3us / cm, and the sample is dried at 60°C for 18 hours to obtain a mesoporous silica template.
[0077] (3) Preparation of mesoporous carbon carrier:
[0078] Take 4g of the mesoporous silica template prepared in step (2), add 6g of sugar alcohol, 14g of water and 21mg of acetic acid, mix well, and stir in an oil bath at 40°C for 2h; then raise the temperature to 80°C and stir for polymerization for 8h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 900°C at 2°C / min, and keep warm for 4h. In 200ml, 1M sodium hydroxide solution, stir at 60°C in a water bath for 4h, remove the template, and then filter, wash, and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 900°C at 5°C / min, and keeping warm for 3h.
[0079] Comparative Example 3 - Carbon Black Impregnation Using Sugar Alcohol Only
[0080] The preparation method of the mesoporous carbon carrier of Comparative Example 3 comprises the following steps:
[0081] (1) Preparation of chain-like mesoporous silica:
[0082] ① Weigh 476g of deionized water, 142.7g of methanol and 71.3g of ethylene glycol, mix them evenly, add 22.355g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0083] ② Add 16.832 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, mix and stir for 0.5 h to obtain a mixed solution II;
[0084] ③ Add a solution uniformly mixed with 26.3 g of tetraethyl orthosilicate, 30 g of ethylene glycol and 60 g of methanol, react at 40° C. for 2 h, filter and dry to obtain chain-shaped mesoporous silica.
[0085] (2) Preparation of mesoporous silica template:
[0086] The chain-shaped mesoporous silica prepared in step (1) is placed in an atmosphere furnace for heat treatment, i.e., treated at 550°C for 3h in an air atmosphere; then a pore expansion treatment is performed, i.e., 350ml×1.5M sulfuric acid is added to a round-bottom flask, the solid content is 1%, and the acidification treatment is performed by oil bath heating at 100°C×72h; finally, the sample is washed and dried until the conductivity is less than 3us / cm, and the sample is dried at 60°C×18h to obtain a mesoporous silica template.
[0087] (3) Preparation of mesoporous carbon carrier:
[0088] Take 4g of the mesoporous silica template prepared in step (2), add 6g of sugar alcohol and mix evenly, then stir and mix at 40℃ in an oil bath for 2h; then raise the temperature to 80℃ and stir and polymerize for 8h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 900℃ at 2℃ / min, and keep warm for 4h. Stir in a water bath at 60℃ for 4h in 200ml, 1M sodium hydroxide solution, remove the template, then filter, wash, and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 900℃ at 5℃ / min, and keeping warm for 3h.
[0089] Performance test 1: structural characterization
[0090] The mesoporous silica and mesoporous carbon prepared in Example 1 of the present invention were characterized, and the results obtained are as follows: Figures 1 to 3 As shown. Figures 1 to 3 It can be seen that the preparation method of the present invention can guide the orderly growth of mesoporous silica towards a chain shape, so that when the carbon black is subsequently used for template replication, a mesoporous carbon with the same structure is obtained, and then when the catalyst is subsequently loaded on the mesoporous carbon, an orderly and step-by-step catalyst can be obtained. The total specific surface area of the mesoporous carbon carrier is 1664m 2 / g, the average pore size is 4-7nm, and the average particle size is 100-300nm.
[0091] Performance test 2: catalytic performance test
[0092] The mesoporous carbons of Examples 1-4 and Comparative Examples 1-3 were used to prepare fuel cell platinum-carbon catalysts to demonstrate the application effect of carbon black materials in the preparation of platinum-carbon catalysts. The preparation method of the platinum-carbon catalyst is as follows:
[0093] Dissolve 8.865g of citric acid (molar weight is three times that of platinum) in 100g of ethylene glycol and ultrasonicate until dissolved, add 160.8g of chloroplatinic acid ethylene glycol solution (concentration is 200mg / ml), stir the mixed solution for 1h, and ultrasonicate for half an hour. Add 2g of the above-mentioned modified carbon black, continue stirring and ultrasonicate the mixed solution. Add 20g of potassium hydroxide and 80g of ethylene glycol solution, adjust the pH to alkaline, and continue ultrasonicate for 20min. The mixed solution is reacted in a reaction vessel. After the reaction is completed and cooled to room temperature, add 10wt% nitric acid solution, adjust the pH to less than 4, and continue ultrasonicate for 15min. Finally, the black powder is washed with deionized water and dried to obtain a 60wt% Pt / C catalyst, and the catalyst membrane electrode test is subsequently performed.
[0094] The results obtained are as follows Figure 4 and Figure 5 As shown. Figure 4 It can be seen that Example 1 is the optimal formula of the present invention, wherein Comparative Example 1 is to adjust the post-treatment sequence of silica, using the conventional method of first acid washing and then air burning. Figure 4 It can be seen that the performance of Comparative Example 1 is significantly lower than that of Example 1, and the decrease in low electric density is obvious, indicating that the structure of the mesoporous carbon obtained by the method of acid washing first and then empty burning cannot obtain a platinum carbon catalyst with more exposed surfaces, so the low electric density performance is not ideal; Comparative Example 2 is an experimental method for adjusting the acidification and pore expansion. The present invention preferably uses an oil bath heating method. Comparative Example 2 uses a hydrothermal method to acidify and expand the silica using high temperature and high pressure. Figure 4 It can be seen that the performance of Comparative Example 2 is much worse than that of Example 1 in terms of large current density performance, which indicates that the hydrothermal method is used to strengthen the strength of the silica acid treatment, so that the internal structure of the mesoporous carbon is changed. In the application of the catalyst, the performance of the large current density mass transfer area is not good; Comparative Example 3 is to change the carbon source impregnation method, and the mesoporous silica is impregnated without using a solvent and an initiator. Figure 4 It can be seen that the overall performance of Comparative Example 3 is not ideal. This is because the impregnation with only sugar alcohol cannot make the silica well infiltrated, so the obtained carbon black cannot completely replicate the pore structure of mesoporous silica, making the performance of carbon black unsatisfactory in subsequent applications.
[0095] pass Figure 5 It can be seen that Example 1 is a preferred formula of the present invention, Example 2 is to adjust the mass ratio of methanol and ethylene glycol in the organic alcohol in the silica preparation process, Example 3 is to adjust the mass ratio of the catalyst, surfactant and silicon source in the silica preparation process, and Example 4 is to adjust the mass ratio of the amount of solvent used in the carbon source impregnation to the mass ratio of mesoporous silica. Figure 5It can be seen that the overall performance is not much different, and the catalyst performance is within the existing membrane electrode test error range, which fully demonstrates the consistency and stability of using this process method.
[0096] Performance Test 3: Batch Stability
[0097] The carbon black sampling results of Examples 1-4 and Comparative Example 1 are shown in Table 1 below. At the same time, the templates of Example 1 and Comparative Example 1 were repeated to explore the carbon black sampling quality, and the results obtained are shown in Table 1 below.
[0098] Table 1 Carbon black impregnation formula and sample collection table of repeated samples of Examples 1-4 and Comparative Example 1
[0099]
[0100] It can be seen from Table 1 that after adjusting the template post-treatment process, the sample quality of carbon black fluctuated after acid washing and then empty burning. However, by using the preparation process of the present invention, it can be seen from the sample quality of carbon black in Examples 1-4 that the fluctuation is very small, basically in a stable state, and the stability between batches is achieved. By repeating the templates of Example 1 and Comparative Example 1 to prepare mesoporous carbon, the fluctuation between different groups in the same batch is also small, and stable production is achieved.
[0101] Example 5
[0102] The preparation method of the mesoporous carbon carrier of Example 5 comprises the following steps:
[0103] (1) Preparation of chain-like mesoporous silica:
[0104] ① Weigh 300g of deionized water, 180.3g of methanol and 53.2g of ethylene glycol, mix them evenly, add 14g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0105] ② Add 10 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, mix and stir for 0.5 h to obtain a mixed solution II;
[0106] ③ Add a uniformly mixed solution of 20 g tetraethyl orthosilicate, 21.8 g ethylene glycol and 44.7 g methanol, react at 40° C. for 10 h, filter and dry to obtain chain-shaped mesoporous silica.
[0107] (2) Preparation of mesoporous silica template:
[0108] The chain-shaped mesoporous silica prepared in step (1) is placed in an atmosphere furnace for heat treatment, i.e., treated at 500°C for 8h in an air atmosphere; then a pore expansion treatment is performed, i.e., 350ml×1M sulfuric acid is added to a round-bottom flask, the solid content of the acid wash is 0.76%, and the acid treatment is performed by oil bath heating at 100°C×72h; finally, the sample is washed and dried until the conductivity is less than 3us / cm, and the sample is dried at 60°C×18h to obtain a mesoporous silica template.
[0109] (3) Preparation of mesoporous carbon carrier:
[0110] Take 4g of the mesoporous silica template prepared in step (2), add 8g of sugar alcohol, 12g of water and 10mg of acetic acid, mix well, and stir in an oil bath at 30°C for 3h; then raise the temperature to 80°C, stir and polymerize for 12h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 350°C at 2°C / min, and keep warm for 6h. Stir in a water bath at 80°C for 6h in 300ml, 0.8M sodium hydroxide solution, remove the template, and then filter, wash, and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 900°C at 5°C / min, and keeping warm for 3h.
[0111] Example 6
[0112] The preparation method of the mesoporous carbon carrier of Example 6 comprises the following steps:
[0113] (1) Preparation of chain-like mesoporous silica:
[0114] ① Weigh 360g of deionized water, 123.3g of methanol and 13.8g of ethylene glycol, mix them evenly, add 30g of hexadecyltrimethylammonium bromide, mix and stir for 0.5h to obtain a mixed solution I;
[0115] ② Add 14 g of 4 wt% sodium hydroxide aqueous solution to the mixed solution I, mix and stir for 0.5 h to obtain a mixed solution II;
[0116] ③ Add a uniformly mixed solution of 30 g tetraethyl orthosilicate, 34.2 g ethylene glycol and 68.7 g methanol, react at 80° C. for 2 h, filter and dry to obtain chain-shaped mesoporous silica.
[0117] (2) Preparation of mesoporous silica template:
[0118] The chain-shaped mesoporous silica prepared in step (1) is placed in an atmosphere furnace for heat treatment, i.e., treated at 600°C for 3h in an air atmosphere; then a pore expansion treatment is performed, i.e., 250ml×3M sulfuric acid is added to a round-bottom flask, the solid content of the acid wash is 1.6%, and the acidification treatment is performed by oil bath heating at 100°C×72h; finally, the sample is washed and dried until the conductivity is less than 3us / cm, and the sample is dried at 60°C×18h to obtain a mesoporous silica template.
[0119] (3) Preparation of mesoporous carbon carrier:
[0120] Take 4g of the mesoporous silica template prepared in step (2), add 2g of sugar alcohol, 20g of water and 15mg of acetic acid, mix well, and stir in an oil bath at 50°C for 2h; then raise the temperature to 100°C, stir and polymerize for 8h; grind, transfer to an atmosphere furnace for carbonization treatment, heat to 600°C at 5°C / min, and keep warm for 4h. Stir in a water bath at 80°C for 6h in 200ml, 1.5M sodium hydroxide solution, remove the template, and then filter, wash, and dry to obtain mesoporous carbon; the mesoporous carbon is subjected to a further post-treatment step, heating to 350°C at 5°C / min, and keeping warm for 6h.
[0121] Performance test 4: batch stability
[0122] The carbon black sampling results of Example 5 and Example 6 are shown in Table 2 below.
[0123] Table 2 Carbon black impregnation formula and sample collection table of Example 5 and Example 6
[0124]
[0125] As can be seen from 2, by adopting the preparation process of the present invention, Examples 5 and 6 achieve batch-to-batch stability.
[0126] In addition to the above embodiments, the present invention can achieve the technical effects of the present invention by using the scope defined in the claims. And for specific substances under the broad category of substances, the same technical effects can be achieved, so they are not listed one by one.
Claims
1. A mesoporous carbon support for a fuel cell, characterized in that: The total specific surface area of the mesoporous carbon carrier is 1400-2000m 2 / g, the average pore size is 4-7nm, and the average particle size is 100-300nm.
2. A method for preparing the mesoporous carbon support for fuel cells according to claim 1, characterized in that: The steps include: (1) Preparation of chain-shaped mesoporous silica; (2) heat treating the chain-shaped mesoporous silica in an air atmosphere at 500-600° C. for 3-8 hours, and then acidifying and expanding the pores with sulfuric acid to obtain a mesoporous silica template; (3) The mesoporous silica template is mixed with a carbon source, a low-boiling point solvent having a hydroxyl group and an initiator, and is first stirred and heated at 30-50° C. for 2-3 hours, and then heated and polymerized at 80-100° C. for 8-15 hours. After carbonization, the mesoporous silica template is removed, and heat treatment is performed to obtain a mesoporous carbon carrier.
3. The method for preparing a mesoporous carbon support for a fuel cell according to claim 2, characterized in that: In step (1), the chain-shaped mesoporous silica is prepared by the following steps: ① Evenly mix deionized water, organic alcohol and surfactant to prepare mixed solution I; the mass ratio of deionized water to surfactant is (12-30):1; ② Add the alkaline solution to the mixed solution I and stir for 0.5-1h to obtain the mixed solution II; ③ After mixing the silicon source and the organic alcohol, a mixed solution III is prepared, and the mixed solution III is added to the mixed solution II, and the reaction is stirred at 40-80° C. for not less than 2 hours, and the chain-shaped mesoporous silica is prepared after filtration and drying; the mass ratio of the silicon source to the organic alcohol is 1:(8-15); In the steps ① to ③, the organic alcohol is methanol and ethylene glycol in a mass ratio of (1-4):1, and the mass ratio of the total amount of the organic alcohol to water in steps ① and ③ is 1:(1-2); the mass ratio of the alkaline solution, the surfactant and the silicon source is (0.46-0.7):(0.7-1):
1.
4. The method for preparing a mesoporous carbon support for a fuel cell according to claim 3, characterized in that: The surfactant includes hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide or nonyltrimethylammonium halide; the alkali is sodium hydroxide, potassium hydroxide, ammonia water or triethylamine; and the silicon source is tetraethyl orthosilicate, tetraethoxysilane, tetraisopropoxysilane or dimethoxydiethylsilane.
5. The method for preparing a mesoporous carbon support for a fuel cell according to claim 2, characterized in that: In step (2), the acidification and pore expansion using sulfuric acid is carried out by acid pickling for 48-72 hours under the conditions of acid concentration of 1-3M and pickling solid content of 0.5-2%.
6. The method for preparing a mesoporous carbon support for a fuel cell according to claim 2, characterized in that: In step (3), the mass ratio of the solvent to the mesoporous silica template is (3-5):1, the mass ratio of the initiator to the carbon source is 1:(100-800), and the mass ratio of the mesoporous silica template to the carbon source is 1:(0.5-2).
7. The method for preparing a mesoporous carbon support for a fuel cell according to claim 6, characterized in that: The solvent is water, ethanol, methanol or isopropanol; the carbon source is xylitol, maltitol, glucose or sucrose; and the initiator is acetic acid, oxalic acid, acetic acid, hydrochloric acid or sulfuric acid.
8. The method for preparing a mesoporous carbon support for a fuel cell according to claim 2, characterized in that: In step (3), the carbonization is carried out at 350-900° C. for 4-6 hours.
9. A catalyst for a fuel cell, characterized in that: The catalyst comprises the mesoporous carbon carrier according to claim 1 and platinum loaded on the mesoporous carbon carrier, and the loading amount of the platinum is 40-70%.